Pengaruh Kepercayaan Digital Generasi Z dalam Adopsi Perbankan Mobile - Tajani, Zalena; Prayitno, Sentot Basuki (Universitas Bunda Mulia, 2025)
This research investigates the direct impact of Search Engine Marketing (SEM), consumer engagement, and consumer trust on Generation Z’s purchase intention toward mobile banking services in DK Jakarta. As the use of technology and the internet has increased, mobile banking has developed as one of the primary service offerings of the banks especially to tech-savvy consumers such as Gen Z. Having grown in the age of digital technology, Gen Z tends to use search engines not only for information, but also for discovering services. Given Generation Z’s preference for online research and digital interactions, this study investigates whether SEM enhances visibility and influences purchase decisions, how consumer engagement strengthens relationships with banking brands, and the role of trust in shaping purchasing behavior. This research employs a quantitative method based on the Theory of Planned Behavior (TPB), Technology Acceptance Model (TAM) and the Theory of Reasoned Action (TRA) to analyze 220 non-customers of Bank Mandiri and BRI in DK Jakarta through an online survey. This study employs path analysis with Partial Least Squares Structural Equation Modeling (PLS-SEM) to test direct effects. A closed-ended survey was created based on the validated constructs from previous research, utilizing a 5-point Likert scale to gauge the effectiveness of SEM, consumer engagement, consumer trust, and purchase intention. The data was analyzed to test the significance of the proposed relationships among the variables. The findings demonstrate that SEM, consumer engagement and consumer trust as independent variables significantly and positively affect purchase intention. Through SEM marketing banks could improve their brand visibility which improves brand discoverability and deepening the emotional and cognitive connection with brands through engagement. Trust emerged as the strongest predictor, confirming that security, reliability, and transparency are essential for encouraging Gen Z to adopt mobile banking. This research emphasizes the significance of integrated digital marketing strategies for Gen Z’s digital behavior and offers practical advice for banking institutions to attract this consumer segment through mobile platforms. This study also contributes to academic literature by complementing the body of research with a consolidated view regarding SEMs, consumer engagement, and consumer trust as predictors of a consumer behavior context in the financial technology domain.